An Analysis on Pronunciation Errors Made By First Semester Students of English Department STKIP CBN - Agnes Maria Diana Rafael (English Education Department, 2019)
This study is conducted to find out the pronunciation errors made by the first semester students of English Education Department in STKIP CBN. In conducting the data, the researcher gave the pre-test to the informants, then; the researcher recorded the performances and transcribed the data. The secondary data was gathered from the interview. Based on the data analysis The researcher counted that there are nine types of errors pronunciation made by the subjects. The first error is the subjects substituted a vowel /æ/ and six consonants /kj/,/tʃ/,/ʃ/,/dʒ/ and /ʒ/ with Indonesian sounds. The second error is the subjects substituted some English vowels into Indonesian vowel. The third error is word cognates cases. The fourth is language interference. The fifth is pronouncing the silent consonant /h/. The sixth error is Deleting or omitting some consonants that appeared at the end of some English words. The seventh error is the subjects pronounced the silent consonant /t/ in the word “often”. The eighth error is the subjects added the consonant /r/ at the word, that word doesn’t required the consonant /r/. The last error is some subjects seemed to generalize the pronunciation of the past tense morpheme which is ended by a bound morpheme /ed/. This research is founded that there are three causes of students’ pronunciation error made in speaking English. The first is an interference errors, the second is an intra lingual errors and the last is a developmental error.